Circular RNA circGSK3B Promotes Cell Proliferation, Migration, and Invasion by Sponging miR-1265 and Regulating CAB39 Expression in Hepatocellular Carcinoma - Li, Kai; Cao, Jiacheng; Zhang, Zitong; Chen, Keyan; Ma, Tieliang; Yang, Wenjie; Yang, Shikun; Rao, Jianhua; Zhang, Kai (Frontiers in Oncology, 2020)
Circular RNAs (circRNAs) have important regulatory roles in the development of various cancers. However, the biological functions and potential molecular mechanisms of circRNAs in hepatocellular carcinoma (HCC) are still unclear. In this study, we investigated the role of a new circRNA-circGSK3B (hsa_circ_0003763) and its molecular mechanism in HCC. We found that circGSK3B was highly expressed in HCC tissues and HCC cell lines. Additionally, the expression level of circGSK3B significantly correlated with HCC tumor size and vascular invasion. Functionally, we confirmed that circGSK3B can promote the proliferation, migration, and invasion of HCC cells in vivo and in vitro. In terms of mechanism, we demonstrated that circGSK3B acts as a miR-1265 sponge, positively regulates the target gene CAB39, and promotes the reprogramming of glutamine metabolism, thereby promoting the progression of HCC. Finally, the classic RNA binding protein QKI was observed to participate in the biogenesis of circGSK3B. In summary, we proved that the circGSK3B-miR-1265-CAB39 axis can promote the proliferation, migration, invasion of HCC cells, indicating that circGSKB may serve as a promising diagnostic and prognostic marker in HCC.